KORELASI SOSIODEMOGRAFI DENGAN KEJADIAN STUNTING - Andi Nursiah; Idris Idris (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Stunting is one of the indicators of chronic malnutrition caused by insufficient nutrient intake over a long period of time. This condition is not only related to inadequate food intake but is also influenced by the poor quality of the food consumed. The objective of this study was to determine the correlation between sociodemographic factors and the incidence of stunting. A cross-sectional study design was used in this research. The study was conducted in the service area of the Tanjung Beringin Community Health Center. The study was conducted in April 2025. The study population consisted of mothers with children aged 0–59 months. The sample comprised 90 respondents. The sampling technique used was purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between maternal education (p-value: 0.042) and no relationship between maternal employment (p-value: 0.532) and the incidence of stunting. It is recommended that the community health center provide education to mothers of toddlers and their husbands, and that mothers of toddlers improve their children’s nutritional status and implement stunting prevention measures. Keywords: Toddlers, Mothers' Employment, Mothers' Education